Comparison of sun protection modalities in parents and children. (February 2015) - Mortier, L.; Lepesant, P.; Saiag, P.; Robert, C.; Sassolas, B.; Grange, F.; Lhomel, C.; Lebbe, C.
Abstract: Background: Routine sun protection is recommended to prevent skin cancer. The aims of the present analysis were to assess and compare modalities of sun protection in parents and their children. Methods: EDIFICE Melanoma is a French nationwide observational survey. It was conducted through phone interviews among a representative sample of 1502 individuals aged ≥18 years, using the method of quotas. The survey took place shortly after the summer, from 28 September to 20 October 2011. Results: Of the 1502 subjects interviewed, 1067 reported sun exposure (SE) at least 10 days per year, 748 were parents and 319 had no children. Sun protection measures seemed adequate in both the 'parents' and 'non‐parents' groups: 74% used clothing and 43% used sunscreen, which was reapplied regularly in 57% of cases. Sun protection measures used by SE parents for SE children were superior, both qualitatively and quantitatively, to those used for themselves, i.e., 50% of parents reported using clothing, sunglasses and hats for their children vs. 23% for themselves. In 87% of cases, parents reported regular re‐application of sunscreen for their children vs. 44% for themselves. The sunscreen SPF (Sun Protection Factor) was significantly lower for parents than for their children. Conclusions: Sun protection awareness appears to be globally satisfactory in the French population, with no difference between adults who are parents and those who are not. From both qualitative and quantitative standpoints, French parents use sun protective measures more efficiently for their children than for themselves.